An investigation of the effects of motorcycle-riding experience on aberrant driving behaviors and road traffic accidents-A case study of Pakistan. Issue 1 (2nd January 2022) - Hussain, Muhammad; Shi, Jing; Batool, Zahara
Abstract: This study investigates the effects of motorcycle-riding experience on aberrant driving behaviors and road traffic accidents (RTAs). Pakistan is one of the countries where motorcycle usage is very high. It can be supposed that the aberrant riding behaviors (improper U-turn, wrong overtaking, stopping anywhere on the road, etc.) while riding a motorcycle might be memorized when motorcycle rider switch to vehicle driving, which ultimately cause RTAs. A self-reported web-based questionnaire survey was conducted in Pakistan, and 396 valid responses were received. The 23-item Driver Behavior Questionnaire (DBQ) was designed to measure aberrant driving behaviors. Proportional Odds (PO) model and binary logistic regression model were employed to examine the effects of motorcycle-riding experience on aberrant driving behaviors and RTAs, respectively. Principal component analysis with varimax rotation confirmed a three-factor solution of aberrant driving behaviors of Pakistani drivers; self-willed violations/errors, distracted violations, and risky violations/errors. Distracted violations were found to be significantly influenced by motorcycle-riding experience. In addition to this, some demographic and socio-economic variables were attributable to aberrant driving behaviors. Surprisingly, no direct relationship was found between motorcycle-riding experience and RTAs. However, a significant association was evident between distracted violations and RTAs. A one-unit increase in distracted violations increased the probability of being involved in RTA by 54%. These results offer a new connection of aberrant driving behaviors to motorcycle use that could be valuable for RTAs reduction.